The SAGE handbook of social network analysis - Carrington, Peter J., 1946-.; Scott, John, 1949-. (London : SAGE, 2011)
Instead of consulting a variety of books and journal articles this handbook, edited by genuine leaders in the field, is a one-stop guide to social network analysis that will be used by readers for decades to come.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Social networks; Social sciences -- Network analysis